Analysis Of The Influence Of Accounting Conservatism, Tax Avoidance, Leverage, Profitability, And Company Size On Company Value (A Case Study Of Manufacturing Companies Listed On The Indonesian Stock Exchange (IDX) From 2019 To 2024) - Ananda, Yunisha Ayu; Bakhtiar, M. Rifki (UNIVERSITAS PAKUAN, 2025)
This research aims to find out how accounting conservatism, tax avoidance, leverage, profitability, and firm size on firm value is affect the value of manufacturing companies that make things people buy, which are listed on the Indonesian stock market between 2020 and 2022. How much a company is worth is shown by its Price to Book Value (PBV), and the things that might change it are shown by CA, ETR, DER, ROA, and Ln Total Assets.The way to do this is by using a specific math process with 236 pieces of information, after getting rid of any that were too far off. The results show that profits and how big a company is have a good and clear effect on how much a company is worth. But being careful in accounting, avoiding taxes, and amounts of debt do not have a clear effect. The Adjusted R² number of 9.4% shows that the math only explains a small bit of what changes how much a company is worth. To sum up, those who put money into companies care more about how much money a company makes and how big it is, instead of careful plans or saving on taxes, when they decide how much a company is worth.